HILIRISASI INDUSTRI KOPI BERORIENTASI PASAR CAFE KEPADA MASYARAKAT PETANI KOPI DI DUSUN TUO LIMBUR KABUPATEN BUNGO - Ikhsan Alfarisi; Joko Susanto; H. M. Chotib; Fajar Ifan Dolly; Yasmir .; Deni Handani (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The coffee industry in Indonesia can be said to be stretching, coffee has now become a lifestyle. The mushrooming of coffee shops in various regions in Indonesia is a sign of this. The skyrocketing coffee industry is inseparable from the development of the world coffee industry, which until now the quality coffee commodity has become the target of both national and international coffee entrepreneurs, including in the city of Muara Bungo. The problem of the coffee industry in Bungo district in general is the difficulty in finding local coffee raw materials, so that opportunities for local coffee farmers who are in accordance with the demands of business actors in the coffee sector to increase the selling value of coffee are wide open. This article describing the problems of coffee processing for the quality of coffee beans from the farmers to entering the coffee industries in the city of Muara Bungo. To achieve this goal, it is necessary to carry out counseling / training on coffee cultivation and coffee processing practices in accordance with the standards of market demand for cafes in the city of Muara Bungo. The enthusiasm of the participants in participating in this training was very impressive, this could be seen from the questions submitted by the training participants regarding good and quality oriented coffee cultivation, the participants got new insights and experiences, including knowing coffee bean processing techniques in accordance with cafe market demand in Muara Bungo city, the distribution channel to the cafe market as well as the desired coffee processing and serving practices of the cafe market as well as through this activity bridging coffee beans from farmers to coffee roasters in the city of Muara Bungo. Some of coffee beans from the farmers in Tuo Limbur was distributed to coffee roasters in the city of Muara Bungo.